Capillary hydrodynamic fractionation of hydrophobic colloids: Errors in the estimated particle size distribution - Clementi, Luis Alberto (2014)
Capillary hydrodynamic fractionation (CHDF) with turbidity detection at a single wavelength is an ana-lytical technique that is often used for sizing the sub-micrometric particles of hydrophobic colloids. Thisarticle investigates three sources of errors that affect the particle size distribution (PSD) estimated byCHDF: diameter calibration errors, uncertainties in the particle refractive index (PRI), and instrumentalbroadening (IB). The study is based on simulated and experimental examples that involve unimodal andbimodal PSDs. Small errors in the diameter calibration curve can produce important deviations in thenumber average diameter due to systematic shifts suffered by the PSD modes. Moderate uncertainties inthe PRI are unimportant in the analysis of unimodal PSDs, but in the specific case of bimodal PSDs, errorsin the PRI can strongly affect the estimated number concentration of each mode. The typical IB correc-tion (based on the IB function estimated from narrow standards) produces slightly erroneous averagediameters but can lead to PSDs with underestimated widths and distorted shapes. In practice, the threeinvestigated sources of errors can be present simultaneously, and uncertainties in the average diameters,the shape and width of the PSD, and the number concentration of the PSD modes are unavoidable.